Clinical and demographic data and the significance of various dysfunctions and severity indicators in multiple sclerosis patients - Gennadii M. Chupryna; Natalia V. Khanenko (Ukrainian Neurosurgical Journal)
Introduction: Visual and oculomotor disorders are frequent manifestations of nervous system damage in multiple sclerosis. Multiple sclerosis is associated with an increased risk of falls, degeneration of sensory organization, and a possible increased reliance on vision for balance control. The clinical picture of multiple sclerosis is characterized by numerous neurological symptoms, among which visual and oculomotor disorders occupy a significant place. This is because the consequences of inflammation, demyelination, and neurodegeneration often negatively affect both the afferent and efferent parts of visual function, significantly worsening the quality of life of patients with multiple sclerosis. Objective: To determine the clinical and demographic characteristics, the significance of nervous system dysfunction and disability, the degree of visual and oculomotor impairment, severity of pain, fatigue, depression, and cognitive impairments, quality of life indicators in patients with multiple sclerosis and to identify the peculiarities of their course in terms of comorbidity. Materials and methods: A total of 216 patients with various forms of multiple sclerosis were examined. Clinical-demographic data, paraclinical characteristics of nervous system dysfunction and disability, severity of pain, fatigue, depression, cognitive disorders and quality of life indicators were analyzed. Patients were assessed using the Functional System Scale (FS), Expanded Disability Status Scale (EDSS), an extended neuropsychological examination. The presence and duration of comorbid diseases were clinically determined through laboratory and instrumental studies, as well as examinations by other specialists (ophthalmologist, therapist, cardiologist, rheumatologist, urologist, and dentist). Results: When conducting a study of patients with multiple sclerosis of the general sample, symptoms associated with pyramidal functions impairment were in 191 patients (88.4%), symptoms caused by the cerebellar functions impairment - in 178 patients (82.4%), symptoms caused by brainstem and cranial nerve dysfunction – in 161 patients (74.5%), symptoms associated with impaired sensitivity functions – in 169 patients (78.2%), symptoms due to pelvic disorders – in 187 patients (87.0%), symptoms caused by impaired visual functions – in 116 patients (53.7%), symptoms associated with impaired cerebral (mental) functions – in 184 patients (85.2%). In total, visual disorders were recorded in 116 (53.7%) patients with multiple sclerosis, among them - in 46 (21.3%) patients of I group (without comorbidity) and in 70 (32.4%) patients of II group (with presence of comorbidity), and oculomotor disorders - in 168 (77.8%) patients with multiple sclerosis, among them - in 77 (35.6%) patients of group I (without comorbidity) and in 91 (42.1%) patients of group II (with presence of comorbidity). In patients with multiple sclerosis, according to the data of the FS-3 FS scale (oculomotor disorders), the average indicators were as follows: group I - 1.4 ± 0.3; group II - 1.6 ± 0.3, and according to the FS-6 FS scale (visual disorders), the average indicators were as follows: group I - 0.8 ± 0.2, group II - 1.4 ± 0.3. Conclusions: The prevalence of visual disorders of patients with multiple sclerosis was 56.0%, and oculomotor disorders - 85.2%. Oculomotor disorders were more widely represented in patients with multiple sclerosis, which, in our opinion, is associated with damage to the structures of the posterior longitudinal bundle, which is often affected in multiple sclerosis due to the “dissemination in space” characteristic of the disease. It was found that in patients with multiple sclerosis visual disorders were most clearly correlated with the level of depression and cognitive impairment. Oculomotor disorders in patients with multiple sclerosis were most clearly correlated with levels of fatigue. In the group of patients with multiple sclerosis with comorbid pathology, visual and oculomotor disorders were significantly more prevalent.